THE INFLUENCE OF COLLEGE STUDENTS’ LEARNING STYLE THE QUR’AN MEMORIZING METHOD IN UKM LPTQ UMY - Prihatin, Ayu Umi; Ichsan, Ichsan (Universitas Islam Negeri Mataram, 2022)
It is essential for us to be knowledgeable about learning styles regarding the method of memorizing the Qur'an, because both of them associate with sensory memory entering the five senses. Afterward, we can implement our understanding of learning styles to determine the appropriate method of memorizing the Qur'an. This study aims to determine the effect of learning styles on the method of memorizing the Qur'an in UKM LPTQ UMY students and to determine the proponent and inhibiting factors in that process. Quantitative research methods with sampling techniques were used in this study. The results of the study show that there is an influence of visual, auditory and kinesthetic learning styles on the Al-Qur'an memorization method. It can be seen from the F count = F count = 7.015, which is greater than the F table = 2.81. In addition, it is proven by the value of Sig. F is 0.001 less than 0.05 and there is a contribution of each visual, auditory and kinesthetic learning style to the Al-Qur'an memorization method; visual 18.81%, auditory 0.52% and kinesthetic learning style 14.06%. Accordingly, the R Square value of 0.334 shows that the proportion of the influence of visual, auditory and kinesthetic (VAK) learning styles on the method of memorizing the Qur'an is 33.4%. Therefore, it can be concluded that there is an influence of visual, auditory and kinesthetic learning styles on students on the method of memorizing the Qur'an in UKM LPTQ UMY.